Case of ketoacidosis by a sodium‐glucose cotransporter 2 inhibitor in a diabetic patient with a low‐carbohydrate diet. Issue 5 (20th February 2015) - Hayami, Tomohide; Kato, Yoshiro; Kamiya, Hideki; Kondo, Masaki; Naito, Ena; Sugiura, Yukako; Kojima, Chika; Sato, Sami; Yamada, Yuichiro; Kasagi, Rina; Ando, Toshihito; Noda, Saeko; et al.
Abstract We present a case of a 32‐year‐old diabetic woman with Prader–Willi syndrome who developed severe ketoacidosis caused by a sodium‐glucose cotransporter 2 (SGLT2) inhibitor, a novel class of antihyperglycemic agents, during a strict low‐carbohydrate diet. At admission, a serum glucose level of 191 mg/dL was relatively low, though laboratory evaluations showed severe ketoacidosis. This is the first report of ketoacidosis caused by a SGLT2 inhibitor. It is necessary to not only pay attention when using a SGLT2 inhibitor in patients following a low‐carbohydrate diet, but also to start a low‐carbohydrate diet in patients treated with a SGLT2 inhibitor because of a high risk for developing ketoacidosis.